ANTIOXIDANT POTENTIAL OF TEMULAWAK (CURCUMA XANTHORRHIZA) EXTRACT GEL AS A CANDIDATE FOR WOUND HEALING - Malau, Reghita Claudia; Nasution, Sri Wahyuni; Nasution, Ali Napiah; Widowati, Wahyu; Salfa Nindya, Faradhina; Kusuma, Hanna Sari Widya (Journal of Vocational Health Studies, 2024)
Background: The complete treatment of chronic wounds remains a significant unmet medical need. To expedite the healing of chronic wounds, numerous studies have begun to utilize gels, including hydrogels or sol-gels, which incorporate a combination of antioxidant properties. Curcuma xanthorrhiza is known to contain polyphenolic compounds, which include flavonoids acting as an antioxidant. Purpose: Examine the potential of C. xanthorrhiza extract (CXE) gel as a candidate for wound-healing by measuring its antioxidant activity. Method: Three CXE gel formulas were prepared from different concentrations of CMC-Na (3, 4, and 5%). Each formula consisted of 5% CXE, 15% propylene Glycol, 10% Glycerin, 0.25% Methylparaben, and distilled water. The quality of the CXE gel was tested through homogeneity, spreadability, pH, and viscosity tests. The antioxidant activity was measured by 2,2-Diphenyl-1-picrylhydrazil (DPPH) and 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS)-reducing activity assay in a gel formula that was close the standards. The measurement results were then used in the calculation of antioxidant activity to determine the IC50 value. Result: Formulas 1, 2, and 3 meet the requirements by yielding a homogeneous gel with a spreadability of 5.37 – 5.93 cm, a pH level of 5.87 – 6.10, and a viscosity of 8.800 – 9296.67 cps. The highest DPPH and ABTS percentages were 34.04% and 5.28%, respectively. The IC50 values of CXE gel in DPPH and ABTS were 1973.38 Î¼g/mL and 700.65 Î¼g/mL, respectively. Conclusion: The CXE 1, 2, and 3 gel formula meets the requirements and has the potential to be used as a wound healing therapy through its antioxidant properties.